2021
DOI: 10.3390/ma14112799
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Wear Performance of TiB2 Coated Cutting Tools during the Machining of Ti6Al4V Alloy

Abstract: The machining of Ti6Al4V alloy, especially at low cutting speeds, is associated with strong Built-Up Edge (BUE) formation. The PVD coatings applied on cutting tools to machine such materials must have the necessary combination of properties to address such an underlying wear mechanism. The present work investigates and shows that TiB2 PVD coating can be designed to have certain mechanical properties and tribological characteristics that improve machining in cases where BUE formation is observed. Three TiB2 coa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 41 publications
(54 reference statements)
0
3
0
Order By: Relevance
“…Some studies have shown the predominant formation of surface films of protective tribological ceramics based on nonequilibrium polyvalent protective oxides of titanium, chromium, and aluminum in the surface layers of nitride coatings [ 27 ]. At a contact temperature exceeding 700 C, the oxidation of titanium diboride begins [ 28 , 29 ], and a decrease in adhesive setting can be associated with the formation of tribological films based on boron oxide [ 17 ]. In addition, it has been shown that interaction in oxide structures is possible under these conditions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have shown the predominant formation of surface films of protective tribological ceramics based on nonequilibrium polyvalent protective oxides of titanium, chromium, and aluminum in the surface layers of nitride coatings [ 27 ]. At a contact temperature exceeding 700 C, the oxidation of titanium diboride begins [ 28 , 29 ], and a decrease in adhesive setting can be associated with the formation of tribological films based on boron oxide [ 17 ]. In addition, it has been shown that interaction in oxide structures is possible under these conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Of interest are studies concerning coatings based on titanium diboride, which have high thermal and chemical stability and a sufficiently low coefficient of friction (about 0.4). A significant self-lubricating effect of TiB 2 coatings was observed, associated with forming B 2 O 3 tribe films when interacting with oxygen from the environment [ 17 ], which reduces friction at the tool–chip interface. The coating is positioned as a composition for processing non-ferrous metals, mainly aluminum and titanium, which are characterized by the intensive formation of sticking on the tool cutting edge.…”
Section: Introductionmentioning
confidence: 99%
“…It could also be observed that wave-shaped slip lines were observed around the edge of indentations for all three samples. It was reported that wave-shaped slip lines appeared around the indentation of the higher hardness samples [ 36 , 37 ]. Thus, the indentations of the three samples corresponded to high hardness.…”
Section: Resultsmentioning
confidence: 99%
“…According to the study [22], steel alloys have several exceptional properties, including excellent corrosion resistance in chloride and Sulphur dioxide environments. In recent years, monitoring cutting tool technology has been applied to evaluate the attributes of cutting tool materials to identify the machinability of cutting tool materials that are notoriously difficult to machine [23][24][25]. In addition, stress and cracking are extremely unlikely in these environments.…”
Section: Research Objectivesmentioning
confidence: 99%